Pengaruh Optimism Terhadap Body Image Remaja Putri Pengguna Produk Kecantikan Di Karawang - Edytia Prameswari Aisyah; Marhisar Simatupang; Dinda Aisha (Psikologi Prima, 2023)
In adolescence there are physical changes, such as rapid growth and increase in height, weight, hormonal changes, sexual maturity and increased function of the brain structure. This is a problem that is still felt especially by young women because these teenagers are starting to pay attention to and take an attitude towards their body and appearance. This can be seen from the beauty and body care products from the latest brands and the emergence of beauty and body care products specifically aimed at "teens" or young women, meaning that young women make an effort to take care of their bodies. Efforts to take care of this body certainly affect how teenagers judge or perceive their bodies, this is called body image. One of the factors forming body image is optimism. Optimism is a comprehensive view, in seeing good things, being able to think positively, and easily giving meaning to oneself. This research was conducted to find out whether there is an effect of optimism on body image in young women in Karawang Regency. The hypothesis put forward is that there is an effect of optimism on body image with the assumption that the higher the optimism, the more positive the body image the individual has. The research method used by researchers is a quantitative research method with a sample of 100 young women living in Karawang, data analysis techniques used by researchers are normality test, linearity test, hypothesis test (simple linear regression test), coefficient of determination test and categorization test with the help of SPSS 25.0 software for Windows. The results of this study's data analysis show that there is an influence of optimism on body image in young women in Karawang with a Sig value of 0.003 (p <0.05).